Heart rate variability during pre-competition and competition periods in volleyball players - Podstawski Robert; Boraczyński Michał; Nowosielska-Swadźba Danuta; Zwolińska Danuta (Sciendo, 2014)
Study aim: Regular exercise training is thought to modify cardiac autonomic control. One of the body's responses to training stimuli is heart rate variability (HRV). The use of HRV in the management of sport training is a common practice. The objective of the present study was to assess the impact of the physical activity level on HRV of 1st league national volleyball players prior to and during the competition period.